Hepatitis B virus infection of HepaRG cells, HepaRG-hNTCP cells, and primary human hepatocytes - Ni, Yi; Urban, Stephan (Hepatitis B Virus, 2017)
Here, we describe in detail how to technically perform HBV infection in vitro with these cells. The methods can be used to explore the mechanism of HBV infection and to build an antiviral screening platform suitable for evaluation of drug efficacy in cells that are metabolically close to primary human hepatocytes.
First online: 15 December 2016
Gesehen am 27.09.2018